Responsibility-value alignment in information security governance - Abdul Munir, Rufizah; Talib, Shuhaili; Abdul Molok, Nurul Nuha; Ahmad, Mohd Ridzuan (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper contributes by discussing the categorization of responsibilities of top management in information security to the four (4) leadership characteristics in Islam as defined and showed by the Prophet Muhammad (PBUH). Contemporary studies, mostly from the West explores the responsibilities of the top management in information security. However, without binding the responsibilities to a specific set of virtue ethics, it will only become a set of tasks rather than responsibilities. Therefore, based on the literature review, this paper introduces a conceptual model that describe the categorization of management’s responsibilities in information security governance to the four (4) Islamic leadership principles – Truthfulness, Trustworthiness, Advocacy and Wisdom. This model allows researchers and practitioners to understand and appreciate the accountability of top management in steering information security initiatives in their organizations from Islamic perspective.